TEACHER’S DISCOURSE MARKERS IN ENGLISH CLASSROOM INTERACTION - Irma Yani Lubis; Siti Aisah Ginting; Yeni Erlita (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
This study deals with discourse markers used by teacher in  English  classroom interaction. The objectives of this study were to find out the  types of discourse markers which were dominantly used by teacher and the reasons for the existences of that dominant one. The subject of this research was an English teacher of SMP Swasta Pahlawan Nasional Medan. A descriptive qualitative design was used in this study. The data were collected by observing, recording the utterances of teacher and by interviewing the subject. The data were analyzed based on Fung and Carter’s theory (2007). The result of the data showed that there were four types of teacher’s discourse markers in English classroom interaction i.e. interpersonal, referential, structural and cognitive. Interpersonal were the most dominantly used by the English teacher with 38,94%, referential 25,26%, structural  30,52% and cognitive 5,26%. The reasons why the teacher used interpersonal markers as the dominant one were affected by the presage category (teacher’s belief) and context category (the class in which the teaching process took place). Related suggestions were given to the English teacher to use the appropriate discourse markers in English classroom interaction. This study was beneficial for both teacher and students in English classroom interaction.Keywords: Discourse Markers, Teacher’s Talk, Classroom Interaction